ANALYSIS OF EFFICIENCY AND EFFECTIVENESS OF REGIONAL PUBLIC SERVICE AGENCY (BLUD) FINANCIAL BUDGET ON WORK PRODUCTIVITY AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE (Survey Study at Payaman Community Health Center, Lamongan Regency) - Mahmud Yulianto; Sri Rochani Mulyani; Chevie Wirawan (Sean Institute, 2023)
This research aims to analyze in more depth the efficiency and effectiveness of the Regional Puplic Service Agency (RPSA) financial budget, work productivity and performance of Puskesmas employees at Payaman Puskesmas Lamongan Regency. The subject in this research were employees at Payaman Community Health Center, Lamongan Regency, with a sample of 62 employees at Payaman Community Health Center. The data analysis used is path analysis, correlation coefficient analysis and coefficient of determination analysis. The results of the research show that in descriptive analysis of the Efficiency, Effectiveness, Productivity of Work Programs and Performance of Community Health Center Employees, respondents rated it as good, although statements with low scores were still found. The path analysis model obtained positive path coefficient values between variables, both directly and indirectly. The productivity variable is able to mediate the efficiency and effectiveness variables on employee performance, where the indirect path coefficient value is greater than the direct path coefficient value. Partial hypothesis test results (a) efficiency significantly influences work productivity, (b) effectiveness significantly influences work productivity, (c) work productivity significantly influences employee performance, (d) efficiency directly significantly influences on employee performance and (e) indirectly effectiveness has a significant influence on employee performance. Simultaneously efficiency and effectiveness have a significant influence on work productivity, where th=57.522 > tα.2.00. Work productivity is able to mediate the efficiency and effectiveness of the RPSA financial budget, where t=5.648 > tα.2.00. Meanwhile, the results of the correlation coefficient show a strong relationship (r-0.813) and the coefficient of determination is also strong (66.1%). This shows that work productivity is more dominantly influenced by the variables used as a model in this research, and has implications for high employee performance.